Platform Monitoring Berbasis Web untuk Sistem Stabilitas dan Pelacakan Kapal Nelayan - Tedyyana, Agus; Ratnawati, Fajar; Danuri, Danuri (Publisher: Fakultas Ilmu Komputer, Institution: Universitas Lancang Kuning, 2023)
Fishing activities in the waters of Bengkalis Island face a number of serious problems, including a lack of data during fishing activities and ship accidents caused by delays in information. In response to this problem, this research proposes the development of a